Plutarch's essay on superstition as a socio-religious perspective on street begging (2014)
Plutarch (c.46AD), in his work, Peri Deisidaimoma (On Superstition), presents a striking portrayal of superstition in the First Century. The Philosopher who also served for decades as a priest of Apollo portrays the pernicious effects of some supposed religious practices as worse than the outcome of atheism. His position constitutes a forceful explanation to ostensibly controversial socioreligious behaviours. This article discusses some of the priest’s concerns as well as his rebuff of religious attitudes that are borne out of what he describes as misrepresentation of the gods or superstition. Plutarch’s essay is seen as illustrating a reason for a socio-religious situation in Africa, a continent that shares a similar religious background with the world of the writer. Specifically, with the example of the hard fight against street begging in some parts of Nigeria, the article shows how social reform programmes could fail when effects of traditional African beliefs and cultural practices remain potent.